Pandemi Covid-19: Tantangan Ekonomi dan Bisnis - Sumarni, Yenti (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2020)
The Covid-19 pandemic is currently sweeping the world including Indonesia, which has had various impacts including the economic sector.This study aims to determine the impact of the Covid-19 Economic and Sharia Business challenges in Indonesia. This type of research is a type of library research and using the qualitatif analysis. The results of this study indicate the impact of the Covid-19 Pandemi that occurred on the global economy including the economy in Indonesia. From this pademic impact the decline in demand for sharia products and hampered production of sharia because raw materials come from outside countries, the impact of this pademic affects this hampered the realization of investment. No exception, investors who plan to invest their capital in Islamic businesses. Increasing the risk of Islamic financial institutions from this challenge Sharia economic and business strategies can overcome the impact of the Covid-19 pademic. It is expected that Islamic economic and business actors show empathy and solidarity with stakeholders. Sharia business people compile more profitable business strategies. Sharia business actors utilize and support stimulus programs from the government. Islamic banking and other financial institutions must start revising growth targets, applying digital transaction technology in one solution. Sharia economics and business can play a role in restoring economic shocks by prioritizing the attainment of sharia objectives (sharia maqashid) Keywords: Covid-19 Impact, Indonesian Economy, Sharia Economy and business.